An integrated approach based on oxidative pyrolysis and microwave-assisted digestion for the multi-elemental analysis of coal samples by ICP-based techniques. (15th October 2015) - Balarama Krishna, M.V.; Chandrasekaran, K.; Chakravarthy, S.; Karunasagar, D.
Graphical abstract: . Highlights: Oxidative pyrolysis and microwave-assisted digestion used for complete dissolution of coal samples. Requires diluted acids for determination of 34 elements. NH4 HF2 is a replacement to highly corrosive HF. High sample throughput and useful for routine analysis. Abstract: Complete dissolution of the coal sample has been achieved using an integrated approach based on oxidative pyrolysis (OP) and microwave-assisted digestion (MWD) for the quantitative determination of major to ultra-trace elements by inductively coupled plasma (ICP)-based techniques. The coal samples were initially pyrolysed by heating to ∼500 °C in the presence of an oxygen stream. Subsequently MWD was applied to the pyrolysed coal residue with an acid mixture of 8 mL of 20%HNO3 + 5%HF + 5%H2 O2 or 20%HNO3 + 0.4%NH4 HF2 + 5%H2 O2 . Analysis was carried out by ICP-MS (Be, V, Cr, Mn, Co, Ni, Cu, Zn, As, Rb, Sr, Mo, Cd, Sb, Cs, Ba, W, Tl, Pb, Th, U and REEs) and ICP-OES (Na, K, Ca, Mg, Fe, Al, Sc, Ti). Critical experimental parameters related to OP and MWD were optimized through the analysis of two standard reference materials (SRMs) NIST-1632d and NIST-2685b. Studies with NH4 HF2 have demonstrated that it can be used as a replacement to the highly toxic HF for achieving quantitative recovery (>95%) of most of the elements studied here. The optimized method was subsequently applied to Indian coal samples collected from different coal mines.